2007
DOI: 10.1111/j.1365-2389.2007.00915.x
|View full text |Cite
|
Sign up to set email alerts
|

A review of non‐equilibrium water flow and solute transport in soil macropores: principles, controlling factors and consequences for water quality

Abstract: This review discusses the causes and consequences of 'non-equilibrium' water flow and solute transport in large structural pores or macropores (root and earthworm channels, fissures and interaggregate voids). The experimental evidence suggests that pores larger than c. 0.3 mm in equivalent cylindrical diameter allow rapid non-equilibrium flow. Apart from their large size and continuity, this is also due to the presence of impermeable linings and coatings that restrict lateral mass exchange. Macropores also rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
621
3
7

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 1,033 publications
(651 citation statements)
references
References 283 publications
(402 reference statements)
20
621
3
7
Order By: Relevance
“…A sensitivity analysis showed that flow variability in macropores at higher rainfall intensities markedly reduces water transfer and increases bypass flow. This might give an additional, field-scale explanation for the frequently observed phenomenon of the small transfer rate coefficient calibrated in DPM to simulate non-equilibrium PF and transport (see discussion in Jarvis, 2007). IN 3 M predicted water balance, water content variation, and dye coverage with depth as observed in irrigation and dye tracer experiments at three field sites reasonably well (Weiler, 2005).…”
Section: Field Scalementioning
confidence: 66%
See 3 more Smart Citations
“…A sensitivity analysis showed that flow variability in macropores at higher rainfall intensities markedly reduces water transfer and increases bypass flow. This might give an additional, field-scale explanation for the frequently observed phenomenon of the small transfer rate coefficient calibrated in DPM to simulate non-equilibrium PF and transport (see discussion in Jarvis, 2007). IN 3 M predicted water balance, water content variation, and dye coverage with depth as observed in irrigation and dye tracer experiments at three field sites reasonably well (Weiler, 2005).…”
Section: Field Scalementioning
confidence: 66%
“…Mass transfer under dynamic conditions, with changing directions to and from matrix, might even compensate some of the bias of the first-order term introduced for steady-state conditions, although this potential effect has not been analyzed yet. At least in view of other uncertainties, the inherent inaccuracy of the first-order term may be tolerable from a practical point of view (Jarvis, 2007). However, improved shape factors (see below, Section 4.1.3) and secondorder terms (Köhne et al, 2004a) were also tested.…”
Section: Modelling Of Tracer Transport In Preferential Flow Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Likely, fracture flow increases pollution vulnerability via an overall reduction in both travel time and natural remediationpotential relative to matrix flow, thereby allowing for comparatively rapid transfer of infiltrating water and pesticides. This proposal is theoretically valid (Freeze and Cherry 1979) and well-established regarding fracture and macropore flow, and associated pollutant transport in e.g., clay tills (Jorgensen et al 1998;Jarvis 2007). However, few studies comparing pesticide pollution in aquifers dominated by matrix flow to those dominated by fracture flow have been able to support such a hypothesis (Neil et al 1989;Barbash and Resek 1996).…”
Section: Discussion Pollution Extent Character and Vulnerabilitymentioning
confidence: 86%